DOI: 10.17488/rmib.41.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Computer Interfaces for upper limb motor rehabilitation of stroke patients

Abstract: Brain-Computer Interfaces (BCI) decode users' intentions from the central nervous system and could be applied for upper limb motor rehabilitation of patients that have suffered stroke, one of the main causes of disability worldwide. Despite that research groups have reported the efficacy of these systems, a consensus has not yet been reached regarding their true potential. For this reason, a review of up-to-date assessments of BCI for upper limb stroke rehabilitation is presented from the perspective of analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…Acute ischemic stroke has been the focus of research on detection, 36,37 effective treatment strategies, 38 and improved recovery 39,40 . Endovascular therapy improves outcomes and recanalizes cerebral arteries; yet, its superiority over standard intravenous tPA for disability‐free survival at 3 months is debated 41 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute ischemic stroke has been the focus of research on detection, 36,37 effective treatment strategies, 38 and improved recovery 39,40 . Endovascular therapy improves outcomes and recanalizes cerebral arteries; yet, its superiority over standard intravenous tPA for disability‐free survival at 3 months is debated 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Acute ischemic stroke has been the focus of research on detection, 36 , 37 effective treatment strategies, 38 and improved recovery. 39 , 40 Endovascular therapy improves outcomes and recanalizes cerebral arteries; yet, its superiority over standard intravenous tPA for disability‐free survival at 3 months is debated. 41 Moreover, the study of Fischer et al 42 found that thrombectomy alone was not as effective as the combination of intravenous alteplase plus thrombectomy in achieving successful reperfusion and improving outcomes in patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in motor skills reduces quality of life and hinders carrying out life activities. The drop that occurs is influenced by residue in the muscles of the upper limbs [2]. Post-stroke rehabilitation is the main focus in restoring neuromuscular function and restoring independence to stroke sufferers [3].…”
Section: Introductionmentioning
confidence: 99%
“…Esto denota la dificultad de obtener información clínica y fisiológica de pacientes con EVC durante su proceso de recuperación. También muestra la gran dificultad y necesidad de recursos humanos y tecnológicos especializados necesarios para brindar alternativas terapéuticas a pacientes con EVC usando BCI acopladas a sistemas robóticos, ya que se estima que únicamente 111 pacientes con EVC han recibido una intervención con este tipo de sistemas, principalmente en países como China (Hong Kong), Alemania, y Rusia [134]. Sin embargo, también se observa que una muestra de 10 pacientes significaría cerca de un 10% de la muestra total que se ha analizado a nivel global y, por lo tanto, asumiendo las limitaciones correspondientes, puede aportar información de relevancia.…”
Section: Limitaciones Y Trabajo Futurounclassified